Neferine alleviates P2X3 receptor in rat dorsal root ganglia mediated neuropathic pain. (September 2021) - Dan, Yu; Guo, Hongmin; Zheng, Chaoran; Wu, Baoguo; Guo, Jingjing; Li, Guilin
Highlights: Neferine lowered the upregulated P2X3 receptor in the DRGs of CCI rats. Neferine relieved the mechanical allodynia and thermal hyperalgesia in CCI rats. Neferine alleviates neuropathic pain may be related to the P2X3 receptor. Abstract: Chronic neuropathic pain is caused by tissue damage or nervous system inflammation and is characterized by sensitivity to painful stimuli. P2X3 receptors play an important role in facilitating pain transmission. Neferine is a bisbenzylisoquinline alkaloid isolated from seed embryos of lotus, which has anti-inflammatory and anti-oxidation pharmacological functions. The present research investigated whether neferine relieves neuropathic pain related to the P2X3 receptor in rat dorsal root ganglia (DRGs). Chronic contraction injury (CCI) in rats was used as a model for neuropathic pain. The results indicated that the expression of P2X3 receptor was significantly increased in the DRGs of CCI rats and that mechanical allodynia and thermal hyperalgesia were also enhanced in CCI rats. Neferine markedly lowered the upregulated P2X3 receptor and interleukin-1beta, inhibited the phosphorylation and activation of ERK1/2 in the DRGs of CCI rats, and relieved neuropathic pain. Therefore, neferine alleviates neuropathic pain by downregulating the expression of P2X3 receptor.